Dentistry for babies: Why do parents seek dental care? - Cunha, Robson Frederico [UNESP]; Matos, Jaqueline Xavier [UNESP]; Marfinati, Suzimary Moya A.P. [UNESP] (My University, 2004)
This study investigated what are the main reasons that led parents to enroll children in a clinic for infants. This was studied by consulting 1368 records during the period from July 1996 to August 2001. The predominant reason for enrolling was orientation/prevention followed by other and treatment. This study demonstrated that a program for children from the first year of life encourages parents to have a new vision of dentistry.
Keywords: child health care; controlled study; dental care; dentistry; human; infant; major clinical study; medical record; parent; pediatrics; preschool child; preventive dentistry; Brazil; health care quality; health promotion; motivation; patient attitude; psychological aspect; Dental Care for Children; Healthy People Programs; Humans; Infant; Motivation; Parents; Patient Acceptance of Health Care; Preventive Dentistry; Program Evaluation